Regional autonomy is forum for political education that is reflected in regional head elections - Firstnandiar Glica Aini Suniaprily; Muhammad Aziz Zaelani; Hanuring Ayu Ardhani Putri (Journal of Law Science, 2024)
In regional autonomy, there are three types of delegation of authority, namely, Deconcentration, Decentralization, and Assistance Tasks. Meanwhile, the way to elect legislative members in provinces and regencies / cities, governors, regents / mayors is by direct elections. Often the election of regional heads and legislative members, which is a political product of regional autonomy, still experiences various problems. This research uses a normative juridical research method with a statutory approach, namely an approach carried out by examining all laws and regulations related to the case or legal issue to be studied. In the statutory approach method, it is necessary to understand the hierarchy of laws and regulations and the principles in laws and regulations. In addition to using a statutory approach, the author also uses a library research approach to collect secondary data. Autonomy is not intended for the purpose of separating a region to be able to break away from the Unitary State of Indonesia. The purpose of granting autonomy to the regions is to enable the regions concerned to organize and manage their own households for the benefit of improving the welfare of the community. The conclusion of the paper with the title Regional Autonomy is a Container for Political Education Reflected in the Regional Head Election (Pilkada) is Regional autonomy in this case is a delegation of authority from the Central Government to the Regional Government, which has laws and regulations to bind and regulate its implementation, is a form of equal rights and obligations, and provides the breadth to regulate existing resources in each particular region in order to equalize development and increase the economic power of the region.